Life in the Stage Coach Days at Historic Sherrill's Inn - Blackmun, Ora (Appalachian State University, 1977)
This is a section from a larger work titled "Western North Carolina to 1880: Its Mountains and Its People." This part focuses on paintings by Elizabeth Cramer McClure that hang on the walls of a room in the original Historic Sherrill's Inn in Fairview, North Carolina. The inn, near Hickory Nut Gap, was a way-station for travelers during the 19th century and early 20th century. Present day, the inn was restored as a private home by Mr. and Mrs. G.K. McClure.